Щодо започаткування у Скіфії династії скіфів-царських - Мозолевський, Б.М. (Археологія, 1990)
У статті обгрунтовується гіпотеза про зміну у Скіфії наприкінці VI — на початку V ст. до н. е. династійної лінії верховних царів, внаслідок якої владу на себе перебрали так звані скіфи-царські (сколоти). Локализация упоминаемых Геродотом трех автономных скифских царств вместе с населявшими их племенами и сопоставление с ними трех царей, руководивших скифским войском во время скифо-персидской войны, привели к парадоксальному на первый взгляд выводу: до конца VI — начала V вв. до н. э. Скифию возглавляла династия, происходившая не из скифов царских, считавших, согласно Геродоту, всех прочих скифов своими рабами, а из более древних племен, обитавших на Южном Буге и в Нижнем Поднепровье.
Однако дальнейший анализ археологических материалов и данных письменной традиции в свете современного состояния изученности скифской проблемы убеждает, что династия так называемых скифов царских действительно приходит к власти уже после столкновения Скифии с Дарием I. Воцарение новой династии, с которой в Скифии устанавливается единовластие, было обусловлено социально-экономическим развитием скифской общности и знаменовало собой переход ее от первой (таборной) ко второй (полукочевой) стадии кочевания.
Тем не менее есть все основания полагать, что отмеченное событие по времени совпадает с возвращением в Северное Причерноморье части скифского населения, задержавшегося после переднеазиатских походов на Северном Кавказе. Оно может быть отождествлено только с рассказом Геродота о битве скифского войска при возвращении его якобы из переднеазиатских походов с детьми остававшихся на родине жен скифов и их рабов. Localization of the three autonomous Scythian kingdoms (mentioned by Herodotus) with their tribes and comparison of their relation to three tsars who headed the Scythian army during the Scythian — Persian War has lead to a paradoxical, at first sight, conclusion: till the late 6th — early 5th centuries B.C. Scythia was headed by a dynasty, which had not originated from the tsar’s Scythians, who (according to Herodotus) considered all other Scythians to be their slaves, but from more ancient tribes which inhabited the South Bug and Lower Dnieper Areas.
However, further analysis of archeological material and the data of writing tradition in the light of the present-state knowledge of the Scythian problem convinces that the dynasty of the so-called tsar’s Scythians really came to power after the conflict between Scythia and Dary I. The accession to the throne of the new dynasty, which establishes the autocracy in Scythia was due to the socio-economic development of the Scythian community, and it signified its transition from the first (camp) to the second (half-nomadic) stage of roaming.
Nevertheless we have evefy feasoh to suppose that the mentioned event coincides in time with coming back to the North Black Sea Area of part of Scythian population which stayed too long after the Fore-Asian campaigns in the North Caucasus. This may be only identified with Herodotus’ tale about the battle of the Scythian army, when it was, supposedly, returning from the Fore-Asian campaigns with children of Scythians’ and slaves’ wives who stayed on the native land.